Geographic variation in gorilla limb bones. Issue 95 (June 2016) - Jabbour, Rebecca S.; Pearman, Tessa L.
Abstract: Gorilla systematics has received increased attention over recent decades from primatologists, conservationists, and paleontologists. Studies of geographic variation in DNA, skulls, and teeth have led to new taxonomic proposals, such as recognition of two gorilla species, Gorilla gorilla (western gorilla) and Gorilla beringei (eastern gorilla). Postcranial differences between mountain gorillas ( G. beringei beringei ) and western lowland gorillas ( G. g. gorilla ) have a long history of study, but differences between the limb bones of the eastern and western species have not yet been examined with an emphasis on geographic variation within each species. In addition, proposals for recognition of the Cross River gorilla as Gorilla gorilla diehli and gorillas from Tshiaberimu and Kahuzi as G. b. rex-pymaeorum have not been evaluated in the context of geographic variation in the forelimb and hindlimb skeletons. Forty-three linear measurements were collected from limb bones of 266 adult gorillas representing populations of G. b. beringei, Gorilla beringei graueri, G. g. gorilla, and G. g. diehli in order to investigate geographic diversity. Skeletal elements included the humerus, radius, third metacarpal, third proximal hand phalanx, femur, tibia, calcaneus, first metatarsal, third metatarsal, and third proximal foot phalanx. Comparisons of means and principal components analyses clearly differentiate eastern and western gorillas, indicating that eastern gorillas have absolutely and relatively smaller hands and feet, among other differences. Gorilla subspecies and populations cluster consistently by species, although G. g. diehli may be similar to the eastern gorillas in having small hands and feet. The subspecies of G. beringei are distinguished less strongly and by different variables than the two gorilla species. Populations of G. b. graueri are variable, and Kahuzi and Tshiaberimu specimens do not cluster together. Results support the possible influence of higher-altitude Pleistocene refugia on patterns of geographic variation in gorillas.